Character design guideline / Faryana Mohd Khalis - Mohd Khalis, Faryana (Universiti Teknologi MARA, Kedah, 2018)
Character design animation refers to a figure of human, animals, creatures or objects that displays the sense of strength, weakness, kindness or bad characteristic. A success character can be easily remembered because of the strong and unique personality. In producing character design, students/ designers must go through the design process form thumbnails, Semi-comprehensive, comprehensive and final stage which involve sketches for the development idea, wacom sketch using brush, pen tool tracing, 2D and 3D colouring. Moreover students are required refer to the related references to identify the style of illustrations on strokes, line and colouring techniques before come out with their own. Along with the sketches design process, Students must to study on the character face expression, costume design, accessories, weapon and equipment's.